1976
DOI: 10.1677/joe.0.0710279
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF Α-Melanocyte-Stimulating HORMONE AND TESTOSTERONE ON CUTANEOUS AND MODIFIED SEBACEOUS GLANDS IN THE RAT

Abstract: The effects of alpha-MSH and testosterone propionate on sebum secretion, sebaceous gland volume, dermal lipogenesis, and preputial gland weight and lipogenesis were examined in hypophysectomized rats. Hypophysectomy reduced sebum secretion, sebaceous and preputial gland size, and dermal and preputial gland lipogenesis. The greatest effects were seen on the biosynthesis of wax esters and squalene. Testosterone propionate (TP) increased sebum secretion, sebaceous gland volume and preputial gland weight and lipog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 17 publications
4
36
0
Order By: Relevance
“…α-Melanocytestimulating hormone (α-MSH) has been demonstrated to act as a modulator of the rat preputial gland, a specialised sebaceous gland-like structure of rodents. 62 The presence of both MC-1R and MC-5R which bind α-MSH were detected in primary cell cultures of facial human sebocytes. The expression of MC-5R is weaker than that of MC1-R but it has been shown to be a marker of human sebocyte differentiation, since it is expressed in differentiated, lipid-containing sebocytes only.…”
Section: Effects Of Hormones On Sebaceous Gland Cellsmentioning
confidence: 96%
“…α-Melanocytestimulating hormone (α-MSH) has been demonstrated to act as a modulator of the rat preputial gland, a specialised sebaceous gland-like structure of rodents. 62 The presence of both MC-1R and MC-5R which bind α-MSH were detected in primary cell cultures of facial human sebocytes. The expression of MC-5R is weaker than that of MC1-R but it has been shown to be a marker of human sebocyte differentiation, since it is expressed in differentiated, lipid-containing sebocytes only.…”
Section: Effects Of Hormones On Sebaceous Gland Cellsmentioning
confidence: 96%
“…In hypophysectomized and castrated rats the reduction of sebaceous lipids was fully restored by concomitant administration of α-MSH and testosterone. 116 In a primary human sebocyte culture system it has been reported that α-MSH can stimulate sebocyte differentiation, sebaceous lipid production and expression of MC5R. 117,118 Thus, evidence is provided demonstrating that α-MSH signaling via MC5R act on a common pathway with androgen-dependent expression of MC5R by induction of the signaling cascade via androgen→FGF7/FGF10→FGFR2b→Shh→Gli→MC5R-expression.…”
Section: Sebaceous Gland Atrophy After Postnatal Fgfr2b Deletionmentioning
confidence: 99%
“…The preputial glands (PG) are large sebaceous glands, rich in wax esters, triglycerides, and alkyl-2,3-diacylglycerols and are believed to play a role in behavioral interactions through the release of pheromones (9). In humans, the PG is located in the corona glandis and prepuce and secretes smegma preputii.…”
mentioning
confidence: 99%